The psychological characteristic of professional work of successful and less successful sellers - T M Babaev (Peoples' Friendship University of Russia (RUDN University), 2010)
The results of researching psychological characteristic of sellers' sociability are considered in this article. The qualitative analysis of distinctions in psychological displays of sociability of successful and less successful sellers has proved, that in the first place they are appeared in originality of a set of various variables of sociability, and secondly - in a degree of preference of those or other attributes of sociability realization.